RANCANGAN SISTEM INFORMASI ADMINISTRASI KESISWAAN PADA MADRASAH ALIYAH NEGERI (MAN) OLAK KEMANG KOTA JAMBI - Elzas - (JURNAL AKADEMIKA)
Processing of Student Administration at Madrasah Aliyah Negeri (MAN) Olak Kemang Jambi City, still using manual, and there are still some weaknesses that led to the frequent occurrence of errors in the report preparation Exam Result Card, and the data that is less secured. Based on research at Madrasah Aliyah Negeri (MAN) Olak Kemang city of Jambi, the author tries to design an application design that can be used to facilitate the process that occurs in the data processing of student, including the development system (System Development) by utilizing the technology in data processing student at Madrasah Aliyah Negeri (MAN) Olak Kemang Jambi city.